PENERAPAN METODE RESITASI TERHADAP HASIL BELAJAR DALAM PEMBELAJARAN SOSIOLOGI DI KELAS XI IPS 1 SMA ISLAMIYAH PONTIANAK - Novariyanti, Vitri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study was aimed to analyze application of the method recitation on learning outcomes in sociology subject to the sciences social XI 1 Islamiyah Senior High School Pontianak. The method used was an experimental method, while the design used was Quasy-experimental designwith One-group pretest-postest design. The populations in this study were 59 students of the XI grade. Samples in this study were 29 students of the XI IPS1 grade. The research instrument was learning test outcomes in form of 10 multiple choice questions. Data collection techniques used in this study was the measurement technique. The Hypothesis test results using t-test obtained t-observed (159,32)> t-table (2.048), with the effect size obtained by 0.96. It can be concluded that there are a significant effect in the application of Make a Match Learning Model toward studentsâ€™ learning outcomes in Sociology Education Subjects to the XI IPS 1 grade students.Â Keywords: Application Of The Method Recitation, Learning Outcomes, Sociology Education.